Effects of Repeated Intravenous Ketamine in Treatment-Resistant Geriatric Depression: A Case Series. Issue 2 (March 2019) - Bryant, Kelly A.; Altinay, Murat; Finnegan, Nora; Cromer, Kim; Dale, Roman M.
Abstract: Purpose: There is an immediate need for more sustainable, effective therapies for treatment-resistant depression in patients who do not respond to traditional psychopharmacology. The aim of this study was to determine the efficacy and safety of intravenous ketamine infusions on the elderly population by using a case series of 6 geriatric patients with treatment-resistant depression. Methods: Eligible patients aged 65 to 82 were given a subanesthetic ketamine hydrochloride dose of 0.5 mg/kg delivered intravenously over 40 minutes twice weekly for an acute series. If patients reported a 50% decrease in depression symptoms after the acute series of 2 to 4 infusions, they would be moved to a maintenance series of infusions, which would occur every 2 to 6 weeks on an individual basis. Results: Of the 6 patients given ketamine, 1 failed to respond to the acute treatment phase, 4 responded to the acute infusion phase but failed to sustain a response after a range of 8 to 22 maintenance infusions, and 1 responded to the infusions but relapsed into alcohol use; therefore, treatment was discontinued. Conclusions: The relative safety of intravenous ketamine in the elderly was demonstrated by the mild, transient adverse effects seen by this patient group. The geriatric population is unable to maintain an antidepressant response to intravenous ketamine over time, signifying that ketamine has low efficacy for the elderly.